Microangiography of the Humeral Condyle in Cocker Spaniel and Non-Cocker Spaniel Dogs - Larsen, Linda J.; Roush, J. K.; McLaughlin, R. M.; Cash, W. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
The purpose of this study was to evaluate the blood supply to the humeral condyle of dogs and compare the blood supply of Cocker Spaniel dogs to non- Cocker Spaniel dogs. We hypothesize that there is a congenitally altered blood supply of the humeral condyle in some Cocker Spaniels when compared to the blood supply of the humeral condyle in other breeds of dogs, which leads to abnormal ossification between the medial and lateral aspects of the humeral condyle, and predisposes them to fracture and delayed healing.Microangiography was performed on four Cocker Spaniel and four non- Cocker Spaniel dogs of similar size and weight. Qualitative and quantitative evaluation of the microangiographs of the humeral condyles revealed a decreased vascular density in the medial, midcondylar and lateral aspects of the condyle in the Cocker Spaniel dogs compared to the non-Cocker Spaniel dogs. This decreased vascular density may play a role in the increased incidence of humeral condylar fractures in the adult Cocker Spaniel dog without any or only minor trauma, and in the delayed healing seen in association with these fractures.A microradiographic comparison was made between the blood supply of the humeral condyles of Cocker Spaniel and other breeds of dogs. A decreased vascular density was documented in Cocker Spaniel dogs.
Keywords: Humeral condylar fractures; microangiography; Cocker Spaniels; blood supply